Kras Immunehistochemical Expression In Colorectal Cancer (Journal of Pharmaceutical Negative Results, 2023)
The goal of this study was to look at the expression of KRAS in colorectal cancer tissue samples and see how it correlated with clinicopathological characteristics. The study was designed in two ways: retrospectively and prospectively. Setting: Department of Pathology, Mosul University. From November 2021 to February 2022, 50 Formalin-fixed paraffin-embedded (FPPE) tissue blocks were collected from private pathology laboratories in Mosul, Iraq, from CRC patients who underwent colectomy.Material and method : On paraffin-embedded tissue blocks, 50 instances of CRC were immunohistochemically stained with the KRAS polyclonal antibody. Data was gathered by retrieving clinical and pathology records. The immunohistochemistry analysis results were linked with the clinicopathological factors reported.Results: During 8 monthes ,The study examined a total of 50 cases of colorectal cancer, and the various clinicopathological factors are described below .The mean age (SD) was (54.80) with range between 20-85 years, about (22)44% were female and28( 56%) were male,the overall male:female ratio was 1.2:2 .According to microscopic types ,44(88%) cases of adenocarcinoma and 5 (10%) of mucinous and 1(2%) of neuroendocrine tumor. regarding to histological grading ,10(20%) cases were well differentiated G1 and 29(58%) for moderately differentiatedG2 and 11 (22%)cases were poor differentiated G3.Lymph node metastasis were positive in 23(46%) and free nodal tissie in 27(54%) of cases.Conclusion: KRAS expression was found in advanced cancers in this investigation. The bulk of these cases were adenocarcinomas, with only a few showing mucinous histology. The current research suggests that established KRAS expression is typically detected in quickly dividing cells with the relationship of advanced malignancies